The Politics of Research - Levine, George Lewis; Kaplan, E. Ann (Book collections on Project MUSE., 1997)
The crisis in the humanities and higher education intensifies daily. In this collection, leading scholars demonstrate how the current furor threatens the critical analysis of culture, so vital to a healthy society. They explore the historical sources of the crisis, the relations between politics and research, the responsibilities and possibilities of the academic intellectual, the structure of the institution of the university, the functions and achievements of the humanities, and the development of interdisciplinarity as a catalyst for change. This volume is a necessary resource for understanding the current crisis and for transforming the academy as we approach the twenty-first century.